2019
DOI: 10.3390/cancers11081086
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into Therapies Targeting Angiogenesis in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a malignancy characterized by neoangiogenesis that is determined by an augmented production of proangiogenesis factors by tumor and adjacent cells. This unbalanced angiogenesis process is a key feature of HCC carcinogenesis and progression. Proangiogenic factors also have a relevant role in the generation and maintenance of an immunosuppressive tumor microenvironment. Several therapeutic options for HCC treatment are based on the inhibition of angiogenesis, both in the early/i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 113 publications
0
31
0
Order By: Relevance
“…HCC is a highly angiogenic cancer (71,72), and therefore antiangiogenic therapy is an effective strategy in the treatment of HCC. LOX-L2 inhibitors could be potent combination partners for the antiangiogenic drugs approved for the treatment of HCC such as Cabometyx, Cyramza, Lenvatinib Mesylate, Ramucirumab and Sorafenib Tosylate (73,74). The present study revealed a potential role of LOXL2 in HCC, which may provide new insights into the treatment of HCC.…”
Section: Discussionmentioning
confidence: 51%
“…HCC is a highly angiogenic cancer (71,72), and therefore antiangiogenic therapy is an effective strategy in the treatment of HCC. LOX-L2 inhibitors could be potent combination partners for the antiangiogenic drugs approved for the treatment of HCC such as Cabometyx, Cyramza, Lenvatinib Mesylate, Ramucirumab and Sorafenib Tosylate (73,74). The present study revealed a potential role of LOXL2 in HCC, which may provide new insights into the treatment of HCC.…”
Section: Discussionmentioning
confidence: 51%
“…4 Department of Hepatobiliary and Pancreatic Surgery, The First Affiliated Hospital of Zhengzhou University, No.1, Jianshedong Road, Zhengzhou 450052, Henan Province, China. 5 Laboratory of Pharmacology and Toxicology, School of Pharmaceutical Sciences, Sun Yat-sen University, Guangzhou 510006, China.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…HCC usually develops from diverse chronic liver diseases underlying cirrhosis (including chronic viral hepatitis types B and C, alcohol abuse, aflatoxin exposure and nonalcoholic fatty liver disease) [3] and is one of the highly vascularized solid tumors characterized by a high presence of hypervascularity and vascular abnormalities [4]. Antiangiogenic therapy is a vital therapeutic strategy for HCC, especially advanced HCC, and antiangiogenic therapy for the treatment of HCC is well established and accepted [5,6]. However, the initial resistance or development of resistance remains a major problem, and the reason remains unclear [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, some of the FDA-approved VEGFR-2 inhibitors, including sorafenib (I), regorafenib (II), lenvatinib (III), nintedanib (IV), sunitinib (V) and pazopanib (VI), were employed for clinical studies either alone or in combination with some other chemotherapies for the treatment of HCC [36]. In 2007, sorafenib (I) was approved by the FDA for the treatment of HCC patients.…”
mentioning
confidence: 99%